Beef replacement heifer decision tool - Sachse, John (Kansas State University, 2017)
Sachse Family Angus is both a commercial and registered Angus cow-calf operation in Northeast Kansas and has been in operation since 1935. The end goal in mind is to provide quality female breeding seedstock to other beef producers with the hopes of improving their herds. Successful selection and development of beef replacement heifers have major long term effects on stayability in any herd and can even have a positive impact on the whole herd. The objective of this study is to create a decision tool to determine best heifer selection strategies. Specifically, taking a look at the cost of heifer development under a range of scenarios as it applies to more traditional heifer development. The depth of literature addressing the issue of buying or raising replacement heifers is vast, providing various degrees of analysis to help a producer make the best informed decision. Some economists would argue that no single aspect of beef production management is as complicated, or has such an economic impact as cow culling and replacement heifer decisions (Melton, 1980). Procedures and methods were created to analyze whether a producer should raise or develop their own replacement heifers. One method used in creating a decision tool is an enterprise budget. Enterprise budgeting is the systematic determination and listing of expected outputs, revenues, and costs due to the production processes required to produce one unit of an enterprise for a specified time period. To take this one step further, it is assumed a producer makes choices with respect to the combinations of productive factors and products. Partial budgets include an analysis of net returns from small changes or refinement to a ranch. It focuses on parts that change while building upon an enterprise budget. In essence, it fine tunes current operations while holding all else constant. The benefits of partial budgeting take a look at what will be the new or added revenue if a change is implemented on the ranch and what costs will be reduced or eliminated if taken place. What will be the new or added costs and what revenues will be reduced if a change takes place are also things to keep in mind. Therefore, the result will show a producer the net benefit of the change. In turn, Sachse Family Angus will use this information to build their registered and commercial replacement heifers either by developing their own or purchasing from other breeders. Overtime, this decision will be critical as it will impact their herd for years to come. In conclusion, maintaining a good sound, high functioning beef cow herd means selecting and developing quality replacement heifers to retain in the herd each year. An estimated 20% of heifers born each year at Sachse Family Angus are kept as replacement heifers. When managing home raised heifers or purchased heifers, maintaining costs and keeping them in check is crucial because they represent a large up-front investment. The bottom line of this research is to give the managers at Sachse Family Angus and other operations across the country a decision tool that can be used to analyze their current resources and the resources it will take to develop their own heifers successfully and in the most cost effective way or help them analyze if purchasing their heifers makes the most financial sense.
Keywords: Replacement heifers; Beef; Partial budget; Buy vs. raise; Agribusiness